Konsep Dasar Belajar dalam Pembelajaran Online: Tren, Masalah, dan Solusi - Ghina Ulpah; Gilang Sukma Permana; Tarsono Tarsono; Miftahul Huda; Taufik Maulana (Jurnal Pendidikan Agama dan Teologi, 2024)
Online learning has become a significant trend in modern education. The basic concept of learning in online learning plays a key role in dealing with the challenges and problems that arise along with technological development. The main trend in online learning involves increased accessibility and flexibility. Technological advances allow learners to access course materials from anywhere and at any time. However, emerging issues include lack of social interaction and feelings of isolation. The basic concept of effective learning in online learning should address these issues. This research aims to examine the basic concept of learning in online learning: trends, problems and solutions. This research uses qualitative method with literature study taken from various sources, including print media, electronic media, books and electronic journals. The research technique is done through exploration and journal search through Google Scholar related to the basic concept of learning in online learning. As for primary and secondary sources in the form of scientific papers that have been published with a high credibility index, namely Sinta 2 to Sinta 5. The results of data analysis are taken from a literature review by means of researchers collecting data, and complete information from various data collection procedures and with a specified time. The collected data is analyzed by using descriptive method to reveal the facts of events written in statements derived from the data sources studied. The results show that, online learning is a growing trend in education. The basic concept of effective learning should consider accessibility, interaction, motivation, and evaluation. Careful solutions are recommended to overcome the problems that arise in online learning and ensure a meaningful learning experience for all participants.